KONTIBUSI KOMPETENSI SISWA DAN PEMANFAATAN FASILITAS BELAJAR DI SEKOLAH TERHADAP KESIAPAN BELAJAR SISWA - Shine Suryadi Tanjung; Putra Jaya (Universitas Negeri Padang, 2019)
This study aims to determine the Contribution of Student Competence and the Utilization of Learning Facilities in Schools Against the Learning Readiness of Class X Students in Audio Video Engineering Expertise Program at SMK Negeri 2 Solok. The population of this study were all students of class X audio video engineering skills program at SMK Negeri 2 Solok 2018/2019 academic year, amounting to 60 students. data retrieval using a random sample of 52 students. The research data collection method used documentation and questionnaires shared with students. This data analysis technique uses multiple regression analysis. The results of the study showed that (1) contributing to student competency and the use of learning facilities in schools together contributed 42.51% to the Learning Preparedness of Class X of the Audio Engineering Expertise Program at Solok State Vocational High School, (2) Student competence contributed as much as 22.66% of the Learning Preparedness of Class X Students in the Audio Engineering Expertise Program at Solok State Vocational High School, (3) Utilizing learning facilities in schools jointly contributes 14.06% to Class X Students' Readiness in Audio Engineering Skills Program in Vocational Schools Negeri 2 Solok. So it can be concluded that Student Competence and Utilization of Learning Facilities in Schools Contribute to Learning Readiness at Solok 2 Vocational School.Keywords: Student Competence, Use of School Learning Facilities, Learning Readiness.